Nickel(II) Removal by Phosphorylated Tamarind Nut Carbon. - SRINIVASAN, K.; SUGANTHI, N. (Asian Journal of Chemistry, 2010)
Activated carbon prepared from phosphorylated tamarind nut (PTNC) has been used for the removal of Ni(II) from aqueous system by batch and column experiments. The efficiency of PTNC was compared with commercial granular activated carbon (CAC). The equilibrium adsorption capacity was determined as a function of the solution pH, adsorbent dosage and contact time for both carbons and found to follow Freundlich and Langmuir isotherms. Kinetic studies indicated that the removal process followed reversible first order equation and adsorption of Ni(II) governed by film diffusion process. Desorption of Ni(II) from carbons were also done by 0.3 N HCl. Column studies were conducted in 2.5 cm diameter columns. Under optimum conditions of flow rate and bed height, breakthrough capacities were found out. PTNC was found to be 6 times superior to CAC in the removal of Ni(II). The mechanism of adsorption for Ni(II) on to PTNC was found to follow ion exchange process predominantly and supported by FT-IR. Nickel(II) removal was also confirmed by XRD and SEM studies.